Manajemen Ekstrakurikuler Hizbul Wathan untuk Membentuk Karakter Kepemimpinan Siswa Kelas X SMA Muhammadiyah 2 Yogyakarta - Puji Kusumandari; Nur Rohmah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2018)
This research aims to analyze the implementation of the management of the Hizbul Wathan extracurricular activities include planning, organizing, implementing and monitoring activities in order to form the character of leadership high school students Muhammadiyah 2 Yogyakarta. The results showed that: (1) management of extracurricular activities extracurricular activities in high school Muhammadiyah Yogyakarta 2 i.e. includes planning activities, organizing, implementing and monitoring activities. (2) the factors supporting the management of extracurricular Hizbul Wathan is: support from the school, the availability of competent human resources, adequate infrastructure and facilities, allocating time, and students that followed the event. Factors restricting extracurricular Hizbul Wathan is management: students, i.e. students who rarely follow Hizbul Wathan extracurricular activities, there is a sudden event as well as the existence of activities extracurricular activities collide with Hizbul Wathan. (3) the results of extracurricular activities Hizbul Wathan in SMA Muhammadiyah Yogyakarta 2 i.e. the growing attitude of responsibility, independent and honest nature to students, students are able to understand and apply the material activities in daily activities, and the growing interest of students towards extracurricular activities Hizbul Wathan.